Umfrage: Steuerliche Belastung deutscher Unternehmen – Steuerlast und Verwaltungskosten - Fochmann, Martin; Heile, Vanessa; Huber, Hans-Peter; Maiterth, Ralf; Sureth-Sloane, Caren

Is Consistency the Panacea? Inconsistent or Consistent Tax Transfer Prices with Strategic Taxpayer and Tax Authority Behavior - Diller, Markus; Lorenz, Johannes; Schneider, Georg; Sureth-Sloane, Caren

Tax Burden on German Companies – Income Tax Burden and Administrative Costs - Fochmann, Martin; Heile, Vanessa; Huber, Hans-Peter; Maiterth, Ralf; Sureth-Sloane, Caren

Update zur grunderwerbsteuerlichen Konzernklausel vor dem Hintergrund der jüngsten BFH-Rechtsprechung - Binder, Sebastian; Lorenz, Johannes (Der Konzern)
Es werden die Anwendungsvoraussetzungen des § 6a GrEStG unter Berücksichtigung der jüngsten BFH-Rspr. dargestellt und ein tabellarischer Überblick über die einzelnen Entscheidungen gegeben. Ausgehend von den Urteilsfällen wird auf die grunderwerbsteuerliche Behandlung von verschiedenen Umwandlungen eingegangen. In einem Ausblick wird der Bezug zum aktuellen Gesetzgebungsverfahren zur Reform der GrESt hergestellt.

Tax Misperception and Its Effects on Decision Making - a Literature Review - Blaufus, Kay; Chirvi, Malte; Huber, Hans-Peter; Maiterth, Ralf; Sureth-Sloane, Caren
Previous accounting research shows that taxes affect decision making by individuals and firms. Most studies assume that agents have an accurate perception regarding their tax burden. However, there is a growing body of literature analyzing whether taxes are indeed perceived correctly. We review 127 studies on the measurement of tax misperception and its behavioral implications. The review reveals that many taxpayers have substantial tax misperceptions that lead to biased decision making. We develop a Behavioral Taxpayer Response Model on the impact of provided tax information on tax perception. Besides individual traits, characteristics of the tax information and the decision environment determine the extent of tax misperception. We discuss opportunities for future research and methodological limitations. While there is much evidence on tax misperception at the individual level, we hardly find any research at the firm level. Little is known about the real effects of managers’ tax misperception and on how tax information is strategically managed to impact stakeholders. This research gap is surprising as a large part of the accounting literature analyzes decision making and disclosure of firms. We recommend a mixed-method approach combining experiments, surveys, and archival data analyses to improve the knowledge on tax misperception and its consequences.

2018/2019 Umfrage zur Steuerkomplexität in deutschen Finanzverwaltungen - Bornemann, Tobias; Schipp, Adrian; Sureth-Sloane, Caren

Tax Avoidance and Social Control - Diller, Markus; Lorenz, Johannes; Meier, David (Operations Research Proceedings 2019)
This study presents a model in which heterogenous, risk-averse agents can use either (legal) tax optimisation or (illegal) tax evasion to reduce their tax burden and thus increase their utility. In addition to introducing individual variables like risk aversion or income, we allow agents to observe the behaviour of their neighbours. Depending on the behaviour of their peer group’s members, the agents’ utilities may increase or decrease, respectively. Simulation results show that taxpayers favour illegal evasion over legal optimisation in most cases. We find that interactions between taxpayers and their social networks have a deep impact on aggregate behaviour. Parameter changes such as increasing audit rates affect the results, often being intensified by social interactions. The effect of such changes varies depending on whether or not a fraction of agents is considered inherently honest.

Real Effects of Public Country-by-Country Reporting and the Firm Structure of European Banks - Eberhartinger, Eva; Speitmann, Raffael; Sureth-Sloane, Caren
European regulation mandates public country-by-country reporting for banks and is expected to increase reputational costs in case of tax haven activities. We test whether the availability of additional public information on the locations of banks' subsidiaries reduces their tax haven presence. In a preliminary difference-in-difference analysis we find that indeed, tax haven presence in “Dot-Havens” has declined significantly after the introduction of mandatory public country-by-country reporting for European banks, as compared to the insurance industry which is not subject to this regulation.

How Does Trust Affect Concessionary Behavior in Tax Bargaining? - Eberhartinger, Eva; Speitmann, Raffael; Sureth-Sloane, Caren
We analyze the impact of trust on bargaining behavior between auditor and auditee in a tax setting. We study the effect of interpersonal trust and trust in government on both taxpayer and tax auditor. In an experiment with variation in pairwise trust settings, we find evidence that both kinds of trust affect the bargaining behavior, albeit in different ways. While trust in government increases taxpayers’ tax offers, interpersonal trust may lead to more concessionary behavior of tax auditors moderated by trust in government. Our findings help tax authorities to shape programs to enhance compliance in an atmosphere of trust.

When Do Firms Highlight Their Effective Tax Rate? - Flagmeier, Vanessa; Müller, Jens; Sureth-Sloane, Caren
This study examines the visibility of the GAAP effective tax rate (ETR) in firms’ financial statements as a distinct disclosure choice. Applying a game-theory disclosure model for voluntary disclosure strategies of firms to a tax setting, we argue that firms face a trade-off in their ETR disclosure decisions. On the one hand, firms have an incentive to enhance their ETR disclosure when the ratio offers shareholders “favourable conditions”, for example in terms of higher expected after-tax cash-flows. On the other hand, the disclosure of a favourable low ETR could attract the attention of tax auditors and the public and ultimately result in disclosure costs. We empirically test disclosure behaviour by examining the relation between disclosure visibility and different ETR conditions that reflect different stakeholder specific costs and benefits. While we find that unfavourable ETR conditions are not highlighted, we observe higher disclosure visibility for favourable ETRs (smooth, close to the industry average, decreasing). Additional analyses reveal that this high visibility is characteristic of firm-years with only moderately decreasing ETRs at usual ETR levels, while extreme ETRs are not highlighted. Interestingly and in contrast to our main results, a subsample of family firms do not seem to highlight favourable ETRs.

Steuerliche Maßnahmen als nützliches Mittel zur Bewältigung der Corona-Krise? - Ergebnisse einer Unternehmensbefragung - Heile, Vanessa; Huber, Hans-Peter; Maiterth, Ralf; Sureth-Sloane, Caren (Deutsches Steuerrecht)

Umfrage: Steuerliche Verwaltungskosten, steuerliche Corona-Soforthilfemaßnahmen und Investitionen in der Krise - Heile, Vanessa; Huber, Hans-Peter; Maiterth, Ralf; Sureth-Sloane, Caren

Tax Complexity in Australia – a Survey-Based Comparison to the OECD Average - Hoppe, Thomas (Australian Tax Forum)
This article comprehensively reviews Australia’s corporate income tax complexity as faced by multinational corporations (MNCs) and compares it to the average of the remaining OECD countries. Building on unique survey data, I find that the Australian tax code is considerably more complex than the OECD average, which is mainly due to overly complex anti-avoidance legislation, such as regulations on transfer pricing, general anti-avoidance or controlled foreign corporations (CFC). In contrast, Australia’s tax framework, which covers processes and features such as tax law enactment or tax audits, is close to the OECD average. A more detailed analysis yields further interesting insights. For example, excessive details in the tax code and the time between the announcement of a tax law change and its enactment turn out to be serious issues in Australia relative to the remaining OECD countries.

Tax Complexity in Australia - A Survey-Based Comparison to the OECD Average - Hoppe, Thomas
This article comprehensively reviews Australia’s corporate income tax complexity as faced by multinational corporations (MNCs) and compares it to the average of the remaining OECD countries. Building on unique survey data, I find that the Australian tax code is considerably more complex than the OECD average, which is mainly due to overly complex anti-avoidance legislation, such as regulations on transfer pricing, general anti-avoidance or controlled foreign corporations (CFC). In contrast, Australia’s tax framework, which covers processes and features such as tax law enactment or tax audits, is close to the OECD average. A more granular analysis yields further interesting insights. For example, excessive details in the tax code and the time between the announcement of a tax law change and its enactment turn out to be serious issues in Australia relative to the remaining OECD countries.

2018 Global MNC Tax Complexity Survey - Hoppe, Thomas; Schanz, Deborah; Schipp, Adrian; Siegel, Felix; Sturm, Susann; Sureth-Sloane, Caren

Measuring Tax Complexity Across Countries: A Survey Study on MNCs - Hoppe, Thomas; Schanz, Deborah; Sturm, Susann; Sureth-Sloane, Caren
This paper introduces an index that comprehensively measures the complexity of countries’ corporate income tax systems faced by multinational corporations. It builds on surveys of highly experienced tax consultants of the largest international tax services networks. The index, called the Tax Complexity Index (TCI), is composed of a tax code subindex covering tax regulations and a tax framework subindex covering tax processes and features. For a sample of 100 countries, we find that tax complexity varies considerably across countries, and tax code and framework complexity also vary within countries. Among others, tax complexity is strongly driven by the complexity of transfer pricing regulations in the tax code and tax audits in the tax framework. When analyzing the associations with other country characteristics, we identify different patterns. For example, with regard to GDP, we find a positive association with tax code complexity and a negative association with tax framework complexity, suggesting that highly economically developed countries tend to have more complex tax codes and less complex frameworks. Overall, our tax complexity measures can serve as valuable proxies in future research and supportive tools for a variety of firm decisions and national and international tax policy discussions.

The Relation between Tax Complexity and Foreign Direct Investments: Evidence Across Countries - Hoppe, Thomas; Schanz, Deborah; Sturm, Susann; Sureth-Sloane, Caren; Voget, Johannes
This paper analyzes the association between tax complexity and foreign direct investments (FDI) based on the newly developed Tax Complexity Index (TCI) and its components. For a sample of 15,607 new foreign subsidiaries, we find no association between total tax complexity, as proxied by the TCI, and the location probability. When we decompose the TCI into tax code complexity and tax framework complexity, we find opposing associations. Tax code complexity is positively related to the location probability, while tax framework complexity is negatively related to it. These associations are, for example, driven by the complexity of transfer pricing and loss offset regulations in the tax code and the dimensions guidance, audits, as well as filing and payments, in the tax framework. In additional analyses, we find that the associations are sensitive to certain characteristics, such as country-specific and firm-specific characteristics. For example, the positive tax code association diminishes when tax rates are high. Overall, we are the first to provide empirical evidence on potential cost-benefit tradeoffs of tax complexity for FDI and thereby enhance prior literature, which has primarily focused on the costs of tax complexity.

Steuerkomplexität als Standortfaktor. So komplex ist das Steuersystem in Deutschland - Sureth-Sloane, Caren (AWV-Informationen)

COVID-19 and investor behavior - Ortmann, Regina; Pelster, Matthias; Wengerek, Sascha Tobias (Finance Research Letters)

Country-by-Country Reporting Goes Public - Cui Bono? - Lagarden, Martin; Schreiber, Ulrich; Simons, Dirk; Sureth-Sloane, Caren (International Transfer Pricing Journal)
After the introduction of CbCR – pursuant to the BEPS Project (Action 13) in 2015 –, which was established to reduce the information asymmetry between MNEs and tax authorities of the countries they operate in, now public CbCR – as suggested by the EU Commission in 2016 – is discussed as a next step. Here, the objective is to overcome information asymmetries between MNEs and the general public of the countries they operate in. Starting from the assumption that regulators care about the legitimacy of tax laws, this article evaluates pros and cons of public CbCR. The authors find that from the perspective of information asymmetries, public CbCR increases tax transparency only marginally at best. Accordingly, it is concluded that democracies that are based on the rule of law seem to rely on pillories in terms of public CbCR to enforce fair tax payments.